Implementing ward based clinical pharmacy services in an Ethiopian University Hospital - Mekonnen AB; Yesuf EA; Odegard PS; Wega SS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Background: Clinical pharmacy practice has developed internationally to expand the role of a pharmacist well beyond the traditional roles of compounding, dispensing and supplying drugs to roles more directly in caring for patients. Studies on the activities of the clinical pharmacist in an inpatient ward in resource constrained settings are scarce, however.Objective: To assess ward based clinical pharmacy services in an internal medicine ward of Jimma University Specialized Hospital. Methods: The study was carried out in the internal medicine ward from March to April, 2011 at Jimma University Specialized Hospital. The study design was a prospective observational study where pharmaceutical care services provided by clinical pharmacists for inpatients were documented over a period of two months. Interventions like optimization of rational drug use and physician acceptance of these recommendations were documented. Clinical significance of interventions was evaluated by an independent team (1 internist, 1 clinical pharmacologist) using a standardized method for categorizing drug related problems (DRPs). Results: A total of 149 drug related interventions conducted for 48 patients were documented; among which 133(89.3%) were clinical pharmacists initiated interventions and 16(10.7%) interventions were initiated by other health care professionals. The most frequent DRPs underlying interventions were unnecessary drug therapy, 36(24.2%); needs additional drug therapy, 34(22.8%) and noncompliance, 29(19.5%). The most frequent intervention type was change of dosage/instruction for use, 23(15.4%). Acceptance rate by physicians was 68.4%. Among the interventions that were rated as clinically significant, 46(48.9%) and 25(26.6%) had major and moderate clinical importance respectively. Conclusion: Involving trained clinical pharmacists in the healthcare team leads to clinically relevant and well accepted optimization of medicine use in a resource limited settings. This approach can likely be generalized to other health care settings in the country to improve medication outcomes.